A hybrid approach for aspect‐oriented business process modeling. Issue 8 (22nd January 2018) - Jalali, Amin; Maggi, Fabrizio Maria; Reijers, Hajo A.
Abstract: Separation of concerns has long been an important strategy to deal with complexity when developing a system. Some concerns (like security) are scattered through the whole system, and different modules are tangled to such concerns. These concerns are known as cross‐cutting concerns. When the system in question is a business process, cross‐cutting concerns are aimed at being encapsulated by Aspect‐Oriented Business Process Modeling. However, the state‐of‐the‐art techniques in this field lack efficient mechanisms that (1) support composition of cross‐cutting concerns that can be defined in parallel to (a part of) a process model and (2) enable specifying both mandatory and optional cross‐cutting concerns. To address these limitations, this paper proposes a new Aspect‐Oriented Business Process Modeling approach. The approach is hybrid since it is based on declarative rules to relate imperative cross‐cutting concerns and imperative business process models. The approach is explained, formally grounded with precise semantics, and used accordingly to implement the artifacts that support modeling and enactment of business processes in the proposed fashion as a proof of concept. In addition, the approach is evaluated on the basis of the Technology Acceptance Model during a workshop session. The result shows that participants perceived the approach usable and easy to use. Abstract : This paper introduces a new hybrid business process modeling approach to support encapsulation of cross‐cutting concerns. The approach relates imperative cross‐cutting concerns and imperative business process models through declarative rules. The approach is explained, formally grounded with precise semantics, and used accordingly to implement the artifacts that support modeling and enactment of business processes. In addition, the usability and easy to use aspects of the approach are evaluated based on the Technology Acceptance Model.